2014
DOI: 10.1128/jcm.00511-14
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Infection of Solid Organ Transplant Recipients by a Multidrug-Resistant Klebsiella pneumoniae Isolate Producing the OXA-48 Carbapenemase, Likely Derived from a Multiorgan Donor

Abstract: We describe two cases of bacteremic infections caused by a multidrug-resistant Klebsiella pneumoniae isolate producing the OXA-48 carbapenemase that occurred in two solid organ transplant (liver and kidney) recipients, which was apparently transmitted with the allografts. This finding underscores the risk of donor-derived infections by multidrug-resistant Gram-negative pathogens in solid organ transplant recipients and emphasizes the need for rapid screening of organ donors for carriage of similar pathogens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
24
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 18 publications
1
24
1
Order By: Relevance
“…The kidney transplant recipient was lost to follow up, but the liver transplant recipient was successfully treated. 38 In a more recent study, Mularoni and colleagues reported the outcomes of 14 SOT recipients who received organs from donors with carbapenem-resistant Gram-negative (CRGN; Acinetobacter baumannii or Klebsiella pneumoniae) bacteremia or CRGN infection of the donated organ. No CRGN infections occurred in the 8 recipients who received immediate treatment posttransplant with at least one week of therapy with activity against the CRGN organism (appropriate therapy).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The kidney transplant recipient was lost to follow up, but the liver transplant recipient was successfully treated. 38 In a more recent study, Mularoni and colleagues reported the outcomes of 14 SOT recipients who received organs from donors with carbapenem-resistant Gram-negative (CRGN; Acinetobacter baumannii or Klebsiella pneumoniae) bacteremia or CRGN infection of the donated organ. No CRGN infections occurred in the 8 recipients who received immediate treatment posttransplant with at least one week of therapy with activity against the CRGN organism (appropriate therapy).…”
mentioning
confidence: 99%
“…34 While CRKP infections remain the most common type of CRE infection in SOT recipients, infections due to carbapenem-resistant Enterobacter spp., as well as NDM-and OXA-48-producing K. pneumoniae have also been reported. [35][36][37][38] The epidemiology of CRE infections in SOT has been best studied in liver and kidney transplant recipients. Centers from New York City and Italy have reported that 6-9% of liver transplant recipients develop CRE infection.…”
mentioning
confidence: 99%
“…Thus, we cannot fully exclude the possibility of donor-derived infection vs post-transplant infection in the setting of a local outbreak. Data from our study and others would suggest that transmission of bacterial infection from the donor respiratory tract to non-lung recipients is a relatively rare event,5,8,15 and our study was likely too small to estimate accurately the risk of disease transmission in this setting.However, collecting respiratory culture samples from non-lung donors, performing culture and susceptibility testing, and reviewing and communicating the results of these cultures requires significant laboratory and personnel resources. 14 Although we would not typically expect a positive donor respiratory culture to confer risk of infection to an abdominal organ transplant recipient, transmission of respiratory tract bacteria from donor to non-lung recipients has occurred in the absence of donor bacteremia 15 ; it is also possible that the donor also had unrecognized MDR Klebsiella gastrointestinal carriage or even bacteremia that was not detected on routine organ recovery culture.Enterobacteriaceae accounted for a large percentage of positive ETA cultures in our study and were significantly more prevalent in ETA culture vs BAL culture, with non-Klebsiella Enterobacteriaceae and Klebsiella spp.…”
mentioning
confidence: 80%
“…2,[5][6][7][8] To date, studies have not investigated the prevalence of MDR/XDR gram-negative colonization among large cohorts of deceased organ donors or the impact of donor colonization on subsequent graft recipient management and outcomes. 2,[5][6][7][8] To date, studies have not investigated the prevalence of MDR/XDR gram-negative colonization among large cohorts of deceased organ donors or the impact of donor colonization on subsequent graft recipient management and outcomes.…”
mentioning
confidence: 99%
“…In the 15 published cases of donor-derived CR-KP infection in solid organ transplant (5 kidneys, 5 livers, 3 lungs, 1 combined liver-kidney, and 1 heart), 13 had an uneventful outcome while 2 recipients died (one after receiving a lung from an asymptomatic carrier of CR-KP in the respiratory tract and one after receiving a kidney from a donor with CR-KP urine infection) [35, 7, 8]. These initial experiences suggest that, in well-defined conditions and following a strict follow-up, organs from colonized CR-KP donors may be considered for transplantation, avoiding their use when the donor's blood cultures were positive or when the organ is directly involved in CR-KP infection, such as lungs in the case of the airway infection or kidneys in urinary tract isolation [7, 8]. …”
Section: Discussionmentioning
confidence: 99%